Does BOC`'s Characteristics Moderate The Effect of Corporate Social Responsibility on Performance? - Muhammad Taufik; Tommy William (Pusat P2M Politeknik Negeri Batam, 2021)
This study investigates the moderation of BOC`'s size and education level the relationship between corporate social responsibility (CSR) and performance which is proxied on Tobins Q, ROA, and ROE. The investigation was observed using the resource dependency theory (RDT) and stakeholder theory paradigms. Data were collected from mining companies listed on the Indonesia Stock Exchange for the 2015-2019 period with a total of 735 data and regressed using panel data techniques. The insignificant effect was found between CSR towards Tobins Q and ROA that indicate mining company focused on reputation and comply to regulatory than moral values. Meanwhile, CSR has significant effects to increase ROE that indicates mining companies tend to approach capital owners. BOC`'s size was unpredispose to moderate between CSR and Tobins Q, ROA, ROE that confirm BOC dodge CSR around. The extremity point is BOC`s education level has negative moderate between CSR and Tobins Q. The key strength of this work adds to the growing literature body of BOC`s characteristics moderate CSR on performances types and has demonstrated the impartiality in CSR.